Aabrm1-mediated melanin synthesis is essential to growth and development, stress adaption, and pathogenicity in Alternaria alternata - Li, Rong; Li, Yongcai; Xu, Wenyi; Liu, Wenjuan; Xu, Xiaobin; Bi, Yang; Prusky, Dov (Frontiers in Microbiology, 2024)
Scytalone dehydratase (brm1) is one of the key enzymes in 1, 8-dihydroxynaphthalene (DHN) melanin synthesis, which mediates melanin biosythesis and regulates cell biological process of plant fungi, but its function in Alternaria alternata, the causal agent of pear black spot, is unclear. Brm1 in A. alternata was cloned, identified, and named as Aabrm1. An Aabrm1-deletion mutant was generated and revealed that the deletion of Aabrm1 leads to a significant decrease in melanin production and forms orange colony smooth spores. In addition, the deletion of Aabrm1 gene impaired infection structure information and penetration. The external stress resistance of ΔAabrm1 was significantly weakened, and, in particular, it is very sensitive to oxidative stress, and the contents of H2O2 and O2.- in ΔAabrm1 were significantly increased. Virulence of ΔAabrm1 was reduced in non-wound-inoculated pear leaves but not changed in wound-inoculated pear fruit. These results indicated that Aabrm1-mediated melanin synthesis plays an important role in the pathogenicity of A. alternata.